Financial Performance Analysis of PT. Tjiwi Kimia Tbk. and PT. Indah Kiat Pulp & Paper Tbk. - Ramadhan, Yanuar; Fauzan, Alfian Kurnia; Rosianwar, Ajeng Kusuma; Metyasari, Dewi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research was prepared to obtain an analysis and compare the financial performance of two large issuing companies in the pulp and paper industry, namely PT. Tjiwi Kimia Tbk. and PT. Indah Kiat Pulp & Paper Tbk. by using the 2022 and 2023 financial reports as a data source. The method used is financial ratio analysis which includes liquidity, solvency, and profitability ratios. Based on the results of an in-depth study, it can be stated that PT. Indah Kiat Pulp & Paper Tbk. has better performance in terms of liquidity with a current ratio of 2.65 in 2023, compared to PT. Tjiwi Kimia which has a current ratio of 1.24. However, in terms of solvency, PT. Tjiwi Kimia has a lower debt-to-equity ratio (DER), namely 0.51 times compared to PT Indah Kiat of 0.69 times, indicating that PT Tjiwi Kimia's financial risk is relatively smaller. In terms of profitability, both companies are seen to have proven positive performance. PT Indah Kiat's net profit margin in 2023 will be 11% with an ROE of 14.6%, while PT Tjiwi Kimia posted a net profit margin of 8.7% with an ROE of 13.6%. However, both PT Indah Kiat and PT Tjiwi Kimia still need to improve operational efficiency and manage financial risks prudently, especially regarding debt management.